Phytosterolaemia associated with parenteral nutrition administration in adult patients. Issue 12 (28th June 2020) - Llop-Talaveron, Josep M.; Leiva-Badosa, Elisabet; Novak, Ana; Rigo-Bonnin, Raúl; Ticó-Grau, Josep R.; Suñé-Negre, Josep M.; Suárez-Lledó, Ana; Lozano-Andreu, Toni; Badía-Tahull, Maria B.
Abstract: Vegetable lipid emulsions (LE) contain non-declared phytosterols (PS). We aimed to determine PS content depending on the brand and LE batch, and in adult hospitalised patients treated with parenteral nutrition (PN), to establish the association between plasma and administered PS. Part I was the LE study: totals and fractions of PS in three to four non-consecutive batches from six LE were analysed. Part II was the patient study: patients with at least 7 previous days of PN with 0·8 g/kg per d of an olive/soyabean (O/S) LE were randomised (day 0) 1:1 to O/S or 100 % fish oil (FO) at a dose of 0·4 g/kg per d for 7 d (day 7). Plasma PS, its fractions, total cholesterol on days 0 and 7, their clearance and their association with PS administered by LE were studied. In part I, LE study: differences were found in the total PS, their fractions and cholesterol among different LE brands and batches. Exclusive soyabean LE had the highest content of PS (422·36 (sd 130·46) μg/ml). In part II, patient study: nineteen patients were included. In the O/S group, PS levels were maintained (1·11 (sd 6·98) μg/ml) from day 0 to 7, while in the FO group, significant decreases were seen in total PS (−6·21 (sd 4·73) μg/ml) and their fractions, except for campesterol and stigmasterol. Plasma PS on day 7 were significantly associated with PS administered ( R 2 0·443). PS content in different LE brands had great variability. PS administered during PN resulted in accumulation and could be prevented with the exclusive administration of FO LE.